Анализ влияния конструктивных параметров автомобиля и параметров движения на область устойчивости адаптивной системы управления торможением - Шуклинов, С. Н. (НТУ "ХПИ", 2014)
Представлены результаты анализа влияния конструктивных параметров автомобиля и параметров движения на область устойчивости адаптивной автоматической и автоматизированной системы управления торможением. Рассмотрены адаптивные тормозные системы с автоматизированным и частично автоматизированным тормозными приводами, в случае адаптивного регулятора воздействующего на основной контур управления и в случае его интегрирования в основной контур управления.

The change of the degree of loading, the efficiency coefficients of brake mechanisms, the efficiency coefficients of brake circuits and other design parameters of the vehicle, as well as the change of motion parameters influence the effectiveness of the brake control. The adaptive brake control system in the event of the wheel rolling in the pre-extreme mode allow forming an invariant control under the action of disturbing factors and as a result improve the quality of the brake control. In this case, there improve the ergonomic indexes of the brake control, reduces the rate and extent of the driver’s fatigue, and as a consequence there increases the safety of vehicle traffic. The effectiveness of the braking control in case of the wheel rolling in the pre-extreme mode is determined by the region of stability of the adaptive control system. The space of parameters forming the region of stability of the brake control system is determined by the structure of the control system and the adjustment algorithm of the adaptive regulator. The block diagram of the adaptive automatic regulation and the scheme of adaptive automated vehicle brake control systems are presented. The mathematical description of the algorithm of the adaptive controller tuning is offered. The adaptive automatic control system is considered for both in case of adaptive controller acting on the main control loop, and in case of its integration into the main control loop. An example of the analysis of the influence of design parameters of the UAZ motor vehicle and control parameters on the stability region of the brake control system is suggested.
The analysis of the influence of design parameters of the vehicle and motion parameters on the stability region of adaptive brake control system
Keywords: автомобили; торможение; адаптивная система; система управления; vehicle; braking; adaptive system; control system; glow down; control error; correcting impact